Mesopic rod and S-cone interactions revealed by modulation thresholds - Zele, Andrew J.; Kremers, Jan; Feigl, Beatrix (Journal of the Optical Society of America A-Optics Image Science and Vision, 2012)
We analyzed mesopic rod and S-cone interactions in terms of their contributions to the blue-yellow opponent pathway. Stimuli were generated using a four-primary colorimeter. Mixed rod and S-cone modulation thresholds (constant L-, M-cone excitation) were measured as a function of their phase difference. Modulation amplitude was equated using threshold units and contrast ratios. This study identified three interaction types: (1) a linear and antagonistic rod:S-cone interaction, (2) probability summation, and (3) a previously unidentified mutual nonlinear reinforcement. Linear rod:S-cone interactions occur within the blue-yellow opponent pathway. Probability summation involves signaling by different postreceptoral pathways. The origin of the nonlinear reinforcement is possibly at the photoreceptors.
EVALuna2:21077